Sound Metric Proximity Hearing App - Revathy, S.P.; Harini, M.; Pooja, J. (Journal of Trends in Computer Science and Smart Technology, 2024)
Globally, hearing impairment affects over 466 million people, creating barriers to accessing audiometric testing and timely diagnosis. Conventional methods often prove challenging to access, especially for people with limited resources or any other disadvantages. The proposed innovative "Sound Metric Proximity Hearing App" aims to revolutionize auditory health through mobile technology. Utilizing advanced techniques such as frequency-specific sound generation, individual ear sound production, and obstacle detection, the app provides comprehensive hearing tests through a user-friendly platform. The application is developed using React Native for the frontend and Django for the backend. It integrates seamlessly with mobile devices and databases, ensuring efficient and reliable performance. With simple result export and tools for early detection, the application enhances the accessibility and efficiency in hearing assessments. It bridges gaps in traditional testing methods, empowering users to proactively manage their auditory health. The "Sound Metric Proximity Hearing App" addresses the essential need for accessible, efficient hearing tests, making a positive impact on global auditory health. Through its innovative approach, the app aims to reduce the stigma associated with hearing loss and promote early intervention. By providing a convenient tool for educators, the app supports classroom management and improves learning environments. With its potential to reach unprivileged people and enhance awareness, the proposed sound metric application is devised to contribute significantly to global auditory health.
Keywords: Digital Audiometer; Mobile Application; Hearing Assessment; Proximity Testing; Classroom Management